THE READERS' ATTITUDE TOWARDS THE REALIZATION OF BAHASA INDONESIA - ENGLISH CODE SWITCHING IN LOOKS MAGAZINE - Novitasari, Meifahmi Intan (2013)
The present study entitled The Readers' Attitude towards the Realization of Bahasa Indonesia - English Code Switching in LOOKS Magazine aims to investigate types and functions of code switching used in "Mailbox" and "Readerstyle" columns of LOOKS magazine and the readers' attitude towards the code switching. Document analysis was occupied to classify types and functions of code switching in the magazine whereas questionnaires were distributed to find out the readers' attitude towards code switching in the magazine. Ten students from English Education Department are purposively chosen as the respondents. The collected data were analyzed by applying some theories. The theory proposed by Poplack (1980) was utilized to analyze the types of code switching; Koziol's theory (2000) was employed to investigate the functions of code switching and the theory of Garret (2010) was applied to explore the readers' attitude towards code switching. The findings reveal that intra-sentential switching dominates the discourse in the magazine (62.50 %). Meanwhile, Emphasize function tends to be the most frequent function occurs in the magazine (45.39 %). Regarding the readers' attitude, it is discovered that the majority of the respondents seem to have a positive attitude towards code switching in the magazine.